Liberdade e opressão em De amor y de sombra e Uma varanda sobre o silêncio - Rossi, Cristiane Aparecida da Rosa (2015)
Since 1964 and 1973, Brazil and Chile, respectively, were taken over by civil-military dictatorship as a consequence of the confrontation of poles of power instituted in the world after the end of the Second World War (1939-1945) and the beginning of the Cold War (1945-1991). Authoritarianism, according to Umbach (2012), consists in a political regime in which the state controls the society, manipulating its political participation and narrowing the possibilities of social mobilization. The present study intends to analyze the sociopolitical contexts of the literary works De amor y de Sombra, written by Isabel Allende (1942), and Uma varanda sobre o silêncio, by Josué Montello (1917-2006). Both novels were published in 1984, and in each plot, the main characters are involved, directly or indirectly, with the military dictatorship and its consequences. Based on the study of the novels‟ central characters, the main objective of the work is to problematize the relationship of women within authoritarianism and their submissive social condition under an androcentric and patriarchal institution. Conservative society has traditionally considered procreation and maternity as women‟s main social roles, through which they would be fully integrated in the social world (SWAIN, 2007). The influence of such themes are here considered in relation to Literature and are understood as ways for social transformation. The approach to the methodology used in this study will be comparative analysis of the aforementioned novels, as well as research related to the proposed themes, from Beauvoir (2009), Muraro (1995), and Swain (2007). Results will show that the composition of the female character, when analyzed under from different perspectives, varies in relation to the genre. The final considerations of this study will point to the prelude of new times, in which women abandon the conventional patterns to which they were used to, revealing to the world different ways to face a traditional society, whose political forces, most of the time, were superior to love.